On the Remote Impacts of Mid‐Holocene Saharan Vegetation on South American Hydroclimate: A Modeling Intercomparison - Tiwari, S.; Ramos, R. D.; Pausata, F. S. R.; LeGrande, A. N.; Griffiths, M. L.; Beltrami, H.; Wainer, I.; De Vernal, A.; Litchmore, D. T.; Chandan, D.; Peltier, W. R.; Tabor, C. R. (Geophysical Research Letters, 2023)
Abstract Proxy reconstructions from the mid‐Holocene (MH: 6,000 years ago) indicate an intensification of the West African Monsoon and a weakening of the South American Monsoon, primarily resulting from orbitally‐driven insolation changes. However, model studies that account for MH orbital configurations and greenhouse gas concentrations can only partially reproduce these changes. Most model studies do not account for the remarkable vegetation changes that occurred during the MH, in particular over the Sahara, precluding realistic simulations of the period. Here, we study precipitation changes over northern Africa and South America using four fully coupled global climate models by accounting for the Saharan greening. Incorporating the Green Sahara amplifies orbitally‐driven changes over both regions, and leads to an improvement in proxy‐model agreement. Our work highlights the local and remote impacts of vegetation and the importance of considering vegetation changes in the Sahara when studying and modeling global climate. , Plain Language Summary Paleoclimate modeling offers a way to test the ability of climate models to detect climate change outside the envelope of historical climatic variability. The mid‐Holocene (MH: 6,000 years ago) is a key interval for paleoclimate studies, as the Northern Hemisphere received greater summer‐time insolation and experienced stronger monsoons than today. Due to a stronger MH West African Monsoon, the Saharan region received enough rainfall to be able to host vegetation. The vegetation changes in the Sahara affected not only the local climate but also far‐afield locations through teleconnections in the global climate system. In this study, we simulate the MH climate using four climate models, each with two types of simulations—with and without the Green Sahara. We show that simulations with the Green Sahara capture greater drying over the South American continent than the simulations which only account for changes in orbital forcing and greenhouse gas concentrations. The simulations with the Green Sahara are more in line with proxy reconstructions, lending further support to incorporating vegetation changes as a necessary boundary condition to simulate the MH climate realistically. , Key Points We simulate the mid‐Holocene with and without the Green Sahara using four fully coupled global climate models The mid‐Holocene simulation with the Green Sahara shows intensification of orbitally‐driven changes in precipitation over northern Africa and South America Incorporation of the Green Sahara leads to greater proxy‐model agreement over both northern Africa and South America